New Image Compression Algorithm using Haar Wavelet Transform - R. El Ayachi; B. Bouikhalene; M. Fakir (International Journal of Informatics and Communication Technology (IJ-ICT), 2017)
The compression is a process of Image Processing which interested to change the information representation in order to reduce the stockage capacity and transmission time. In this work we propose a new image compression algorithm based on Haar wavelets by introducing a compression coefficient that controls the compression levels. This method reduces the complexity in obtaining the desired level of compression from the original image only and without using intermediate levels.